IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH CLIL IN TOURIST GUIDING ONLINE CLASS - Novitasari Novitasari; Noverita Wahyuningsih; Hiqma Nur Agustina (University of Muhammadiyah Malang, 2022)
Tourist Guiding is a compulsory subject that aims to prepare students to be a prospective Tour Guide (TG) with excellent English mastery, especially speaking. Two-year observation showed that the students have the low ability in speaking skills. They did not speak fluently because they lacked knowledge and vocabulary in tourist guiding. This study was a Classroom Action Research (CAR) which was carried out by implementing Content and Language Integrated Learning (CLIL), as a dual-educational approach that uses additional languages to learn and teach both content and language, in an online Tourist Guiding class. Participated by 28 students, this research followed stages of CAR. Additionally, pre-test and post-test were conducted to investigate students’ different performances before and after CLIL was implemented, while questionnaires were distributed to obtain the data about the students’ voices about CLIL implementation. The findings revealed that the quality of teaching and learning in the Tourist Guiding class improved after the implementation of CLIL. In addition, CLIL could enhance both students’ language skills (especially speaking) and tourist guiding competency. Teachers should both understand the subject content very well and have a very good mastery of English so that CLIL can be implemented successfully.